2010
DOI: 10.1371/journal.pone.0015045
|View full text |Cite
|
Sign up to set email alerts
|

Acyl-Protein Thioesterase 2 Catalizes the Deacylation of Peripheral Membrane-Associated GAP-43

Abstract: An acylation/deacylation cycle is necessary to maintain the steady-state subcellular distribution and biological activity of S-acylated peripheral proteins. Despite the progress that has been made in identifying and characterizing palmitoyltransferases (PATs), much less is known about the thioesterases involved in protein deacylation. In this work, we investigated the deacylation of growth-associated protein-43 (GAP-43), a dually acylated protein at cysteine residues 3 and 4. Using fluorescent fusion construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
127
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(137 citation statements)
references
References 64 publications
7
127
1
Order By: Relevance
“…This is of interest because removal of the palmitate moieties from the IP3R may serve to increase the turnover of this Ca 2+ channel protein. S-palmitoylation is reversed by acyl protein thioesterases (APTs), mainly the cytosolic enzymes APT1 and APT2 (36,37). In this manner, palmitoylation/depalmitoylation through PATs/APTs may represent an enzymatic process that serves to fine tune the level of Ca 2+ in activated immune cells and thereby regulate immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…This is of interest because removal of the palmitate moieties from the IP3R may serve to increase the turnover of this Ca 2+ channel protein. S-palmitoylation is reversed by acyl protein thioesterases (APTs), mainly the cytosolic enzymes APT1 and APT2 (36,37). In this manner, palmitoylation/depalmitoylation through PATs/APTs may represent an enzymatic process that serves to fine tune the level of Ca 2+ in activated immune cells and thereby regulate immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these thioesterases, acyl-protein thioesterase-1 (APT1) (11) and APT2 (12), are localized predominantly in the cytoplasm, and the other two, palmitoyl-protein thioesterase-1 (PPT1) (13,14) and PPT2 (15), are lysosomal enzymes (16,17). The first cytosolic thioesterase to be characterized was APT1, which cat-alyzed depalmitoylation of the ␣-subunit of G-proteins and proto-oncogene H-Ras product in vitro (11) as well as synaptosomal-associated protein 23 (SNAP-23) (18).…”
mentioning
confidence: 99%
“…The first cytosolic thioesterase to be characterized was APT1, which cat-alyzed depalmitoylation of the ␣-subunit of G-proteins and proto-oncogene H-Ras product in vitro (11) as well as synaptosomal-associated protein 23 (SNAP-23) (18). More recently, a second cytosolic thioesterase, APT2, has been reported to depalmitoylate GAP-43 (growth-associated protein 43) (12). Although both H-Ras and GAP-43 undergo palmitoylation (3,4) for membrane localization, these proteins also require depalmitoylation catalyzed by APT1 and APT2, respectively, to detach from the membrane and to be recycled.…”
mentioning
confidence: 99%
“…The preferred substrates of APT1 were identified as thioacylated proteins (Duncan and Gilman, 1998;Hirano et al, 2009) although APT1 was originally identified as a lysophospholipase (Sugimoto et al, 1996). Further characterisation of human APT1 (hAPT1) has shown that it is responsible for cleaving palmitate from substrates both in vitro and in vivo (Duncan and Gilman, 1998;Tomatis et al, 2010). It is possible that the distinct substrate specificities of APT1 and APT2 are due in part to their differential expression between cell types, although some overlap might exist (Tomatis et al, 2010).…”
Section: Enzymes Implicated In Protein Depalmitoylationmentioning
confidence: 99%
“…Further characterisation of human APT1 (hAPT1) has shown that it is responsible for cleaving palmitate from substrates both in vitro and in vivo (Duncan and Gilman, 1998;Tomatis et al, 2010). It is possible that the distinct substrate specificities of APT1 and APT2 are due in part to their differential expression between cell types, although some overlap might exist (Tomatis et al, 2010). The palmitoylation cycle that controls the correct compartmentalisation of H-Ras and N-Ras is the most intensively studied example of an APT1 substrate (Baekkeskov and Kanaani, 2009).…”
Section: Enzymes Implicated In Protein Depalmitoylationmentioning
confidence: 99%